Genotypic Variation in Grain P Loading across Diverse Rice Growing Environments and Implications for Field P Balances - Vandamme, Elke; Wissuwa, Matthias; Rose, Terry; Dieng, Ibnou; Drame, Khady N.; Fofana, Mamadou; Senthilkumar, Kalimuthu; Venuprasad, Ramaiah; Jallow, Demba; Segda, Zacharie; Suriyagoda, Lalith; Sirisena, Dinarathna; et al. (Frontiers in Plant Science, 2016)
More than 60% of phosphorus (P) taken up by rice (Oryza spp.) is accumulated in the grains at harvest and hence exported from fields, leading to a continuous removal of P. If P removed from fields is not replaced by P inputs then soil P stocks decline, with consequences for subsequent crops. Breeding rice genotypes with a low concentration of P in the grains could be a strategy to reduce maintenance fertilizer needs and slow soil P depletion in low input systems. This study aimed to assess variation in grain P concentrations among rice genotypes across diverse environments and evaluate the implications for field P balances at various grain yield levels. Multi-location screening experiments were conducted at different sites across Africa and Asia and yield components and grain P concentrations were determined at harvest. Genotypic variation in grain P concentration was evaluated while considering differences in P supply and grain yield using cluster analysis to group environments and boundary line analysis to determine minimum grain P concentrations at various yield levels. Average grain P concentrations across genotypes varied almost 3-fold among environments, from 1.4 to 3.9 mg g−1. Minimum grain P concentrations associated with grain yields of 150, 300, and 500 g m−2 varied between 1.2 and 1.7, 1.3 and 1.8, and 1.7 and 2.2 mg g−1 among genotypes respectively. Two genotypes, Santhi Sufaid and DJ123, were identified as potential donors for breeding for low grain P concentration. Improvements in P balances that could be achieved by exploiting this genotypic variation are in the range of less than 0.10 g P m−2 (1 kg P ha−1) in low yielding systems, and 0.15–0.50 g P m−2 (1.5–5.0 kg P ha−1) in higher yielding systems. Improved crop management and alternative breeding approaches may be required to achieve larger reductions in grain P concentrations in rice.